Demographic and clinical features of hidradenitis suppurativa in Turkey - Yüksel, Mavişe; Basım, Pelin (SAGE Publications, 2020)
Background The literature contains conflicting reports on the epidemiology and frequency of hidradenitis suppurativa (HS), a chronic, recurrent inflammatory disease of the apocrine glands. Objective To evaluate the clinical and demographic characteristics of HS cases in Turkey and investigate the similarities with world epidemiology. Method The records of 208 patients that presented to our polyclinics and were diagnosed with HS between June 2012 and July 2017 were retrospectively evaluated. Results Of the cases, 68.3% were male and 31.7% were female. Of the patients, 75.5% had no family history of HS, 60.6% were smokers, 39.4% were aged 20-29 years, and 36.1% were aged 30-39 years. The most commonly involved regions were the axilla (62%), groin (50.5%), and gluteus (15.9%). According to univariate analyses, male patients had higher disease stages than females (odds ratio=1.67). The patients with groin involvement, high body mass index (BMI), and low education level (0-8 years) had higher risk of severe disease stage (odds ratio=1.63, 8.91, and 1.51, respectively). The most commonly used treatment was oral antibiotics in Hurley stages I and II, and surgical intervention in Hurley III. In all 3 Hurley stages, clavulanic acid-amoxicillin combination was the mostly used systemic antibiotic (41.8%, 43.2%, and 47.8%, respectively). Conclusions This is the first epidemiological study on HS in the Turkish population, where HS shows male predominance. Male gender, low education level, absence of acne, high BMI, and groin involvement were associated with severe disease stages. Determining associated comorbidities and possible risk factors is important in progression and prevention of the disease.
Keywords: Turkey; Hidradenitis Suppurativa; Demographics